2009
DOI: 10.1088/1126-6708/2009/07/011
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional black holes, gravitational solitons, kinks and wormholes for BHT massive gravity

Abstract: The theory of massive gravity in three dimensions recently proposed by Bergshoeff, Hohm and Townsend (BHT) is considered. At the special case when the theory admits a unique maximally symmetric solution, a conformally flat solution that contains black holes and gravitational solitons for any value of the cosmological constant is found. For negative cosmological constant, the black hole is characterized in terms of the mass and the "gravitational hair" parameter, providing a lower bound for the mass. For negati… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
267
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 163 publications
(277 citation statements)
references
References 94 publications
10
267
0
Order By: Relevance
“…It turns out that the answer is in the affirmative: In contrast to what happens with other solutions of massive gravity, like the ones found in Refs. [38] and [39], whose boundary stress-tensors can be regularized by introducing additional counterterms, here the geometrical simplicity of the WAdS 3 spaces happens to play against us: For WAdS 3 we havê…”
Section: Countertermsmentioning
confidence: 99%
“…It turns out that the answer is in the affirmative: In contrast to what happens with other solutions of massive gravity, like the ones found in Refs. [38] and [39], whose boundary stress-tensors can be regularized by introducing additional counterterms, here the geometrical simplicity of the WAdS 3 spaces happens to play against us: For WAdS 3 we havê…”
Section: Countertermsmentioning
confidence: 99%
“…Since the OTT solution is known to exists also for positive or vanishing 1/ 2 [12], most of the present results could be straightforwardly extended to these sectors.…”
Section: Discussionmentioning
confidence: 83%
“…Then, we showed that gravitational waves can be naturally incorporated into the PGT dynamical framework [10,11]. The purpose of the present work is to examine a PGT generalization of the Oliva-Tempo-Troncoso (OTT) black hole [12], see also [13], as well as its Vaidya-like extension [14].…”
Section: Jhep05(2015)101mentioning
confidence: 98%
See 2 more Smart Citations